Function of HNRNPC in breast cancer cells by controlling the dsRNA‐induced interferon response. (29th August 2018) - Wu, Yusheng; Zhao, Wenwei; Liu, Yang; Tan, Xiangtian; Li, Xin; Zou, Qin; Xiao, Zhengtao; Xu, Hui; Wang, Yuting; Yang, Xuerui
Abstract: Elevated expression of RNA binding protein HNRNPC has been reported in cancer cells, while the essentialness and functions of HNRNPC in tumors were not clear. We showed that repression of HNRNPC in the breast cancer cells MCF7 and T47D inhibited cell proliferation and tumor growth. Our computational inference of the key pathways and extensive experimental investigations revealed that the cascade of interferon responses mediated by RIG‐I was responsible for such tumor‐inhibitory effect. Interestingly, repression of HNRNPC resulted in accumulation of endogenous double‐stranded RNA (dsRNA), the binding ligand of RIG‐I. These up‐regulated dsRNA species were highly enriched by Alu sequences and mostly originated from pre‐mRNA introns that harbor the known HNRNPC binding sites. Such source of dsRNA is different than the recently well‐characterized endogenous retroviruses that encode dsRNA. In summary, essentialness of HNRNPC in the breast cancer cells was attributed to its function in controlling the endogenous dsRNA and the down‐stream interferon response. This is a novel extension from the previous understandings about HNRNPC in binding with introns and regulating RNA splicing. Synopsis: Repression of RNA binding protein HNRNPC in breast cancer cells MCF7 and T47D resulted in accumulation of endogenous dsRNA species mostly from Alu introns, which triggered interferon response and tumor growth arrest. HNRNPC is highly expressed in breast cancer tumors and repression of HNRNPC arrests proliferation of MCF7 and T47D cells. Interferon response mediated by RNA sensor RIG‐I is responsible for anti‐proliferation effect of HNRNPC repression. Repression of HNRNPC induces immunostimulatory endogenous dsRNA mostly from introns with Alu. Production of Alu dsRNA can be traced back to RNA quality control machinery such as nonsense‐mediated decay. Abstract : Repression of the RNA binding protein HNRNPC in breast cancer cells causes accumulation of endogenous dsRNA species leading to interferon response and tumor growth arrest.